Life beyond the boundaries: constructing identity in edge regions of the North American Southwest - Harry, Karen G., editor; Herr, Sarah A., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
Exploring identity formation in American Southwest communities during pre-contact. Focused on some of the more poorly understood regions using methods drawn from science, anthropology, and history to investigate a variety of themes related to the construction of social identity groups along the Southwest perimeters.--Provided by publisher.
Life beyond the boundaries / Sarah Herr and Karen G. Harry -- Frontiers of marginality and mediation in the North American Southwest: a social networks perspective / Matthew Peeples and Barbara Mills -- Pueblo emergence on the Taos frontier / Severin Fowles -- Sophisticated rebels: meaning maps and settlement structure as evidence for a social movement in the Gallina region of the North American Southwest / Lewis Borck -- Shaping identity in prehispanic southern Nevada / Karen G. Harry and James Watson -- Architectural traditions in the early Pueblo Period Puerco Valley / Kellam Throgmorton -- Enculturation and large-scale group identity from the center to the edge of the late pre-classic Hohokam world / Sarah Herr and Jeffery Clark -- A millennium of identity formation and maintenance in the Jornada Mogollon / Myles Miller -- Long-term, constant, and stable identities and social relationships with and within the Mimbres region of southwestern New Mexico / Patricia Gilman -- Negotiating identity in the wake of European contact in the Pimería Alta / Lauren Jelinek and Dale Brenneman.
Keywords: Indians of North America -- Southwest, Old -- Social conditions; Indians of North America -- Mexico -- Social conditions; Group identity -- Southwest, Old -- History -- To 1500; Group identity -- Mexico -- History -- To 1500; Borderlands -- Social aspects -- History -- To 1500; Social archaeology -- Southwest, Old; Social archaeology -- Mexico